Sibship and self-esteem in children with asthma - Concetta Polizzi; Valentina Fontana; Antonio Carollo; Alessandra Bono; Sofia Burgio; Giovanna Perricone (MDPI AG, 2016)
This study has explored the valence of sibship that may empower the self-esteem of children with asthma at the interpersonal, environmental control competence, emotionality management, and body-image levels. It has been assumed that the relationship between siblings may have a moderating effect on the negative impact that asthma has on child's development. Seventy children suffering from chronic asthma have been involved: 40 children with siblings (experimental group) and 30 sibling-free children (control group). The children with asthma have exhibited higher levels of self-esteem in comparison with the sibling-free children. The results of the study, at the clinical significance level, highlight how meaningful could be the involvement of healthy siblings to support the development, and to ease the compliance of children suffering from asthma. The outcomes have confirmed the supportive valence of sibship for the self-esteem of the children with asthma.